Penguatan Karakter Disiplin melalui Program Amaliah Ubudiah di Madrasah Aliyah - Rossa, Devind Camelia; Hosna, Rofiatul (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
Reprehensible behavior is basically carried out by students who have a low understanding of religion. Through the charity (amaliah ubudiah) program, students can have commendable behavior. This study aims to form a disciplined character through the charity program in students of Madrasah Aliyah Al-Asy'ari Keras Diwek Jombang. This study uses a qualitative method with a descriptive type. Data collection techniques are carried out through observation, interviews, and documentation. The results of this study indicate that; 1) the activity of strengthening the character of discipline through the charity program is carried out through activities that emphasize time discipline, attitude discipline and learning discipline 2) the character of student discipline in this madrasah through the implementation of the charity program through interviews and observations in the field continuously every day and continuously, so it can be concluded that there is a positive impact and a 70% increase in the character of student discipline, 3) the lack of student discipline is caused by several inhibiting factors such as low self-awareness, lack of parental attention and the influence of friendship, in addition there are also supporting factors, namely a good school environment, adequate facilities, and support from parents. This study provides a solution to strengthen the character of student discipline.